Determining the biomass and nutrient content of the invasive Acacia mearnsii and Eucalyptus camaldulensis trees in Fynbos riparian zones - Juba, Roderick (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDConsEcol)--Stellenbosch University, 2020.